Aspectos demográficos de la inmigración (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2013)
This work is divided into three parts. In the first part I analyse the influence that immigration is having on the total growth and on the expansion of the Autonomous Communities. In the second part I present the main demographic characteristics of the recent mobility, its spatial distribution, origins and its age and sex composition.In the third part I explain the current situation of nuptuality, birth rate, fertility and death rate of foreigners and their influence on the same phenomena on regional andnational scale.
Keywords: Immigration; Spain; foreigners; demography